Sulfur-containing compounds and polymers and their use in electrochemical cells
By using a polymer containing disulfide bonds in lithium sulfur batteries to react with elemental sulfur to form an electrochemically active polyimide copolymer, the problem of sulfide dissolution is solved and the cycle stability and electrochemical performance of the battery are improved.
Patent Information
- Application Number
- CN201880064264.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-10-02
- Filing Date
- 2018-10-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2039-01-08
Smart Images

Figure CN111164073B_ABST
Abstract
Description
[0001] Related Applications
[0002] Under applicable law, this application claims priority to Canadian Patent Application No. 2,981,012, filed on October 2, 2017, the entire contents of which are incorporated herein by reference. Technical Field
[0003] The present application relates to the field of polymers and oligomers for use as electrochemically active materials in positive electrodes, as solid polymer electrolytes (SPEs) or as additives to electrolytes, in particular for use in lithium batteries. Background Art
[0004] Global environmental awareness influences numerous scientists to find answers to the greenhouse gas problem and its impact on our planet. Knowing that transportation plays a major role in greenhouse gas emissions, the electrification of transportation is undoubtedly part of the solution to the global warming problem. Therefore, it is important to design a new battery material that is more environmentally friendly, more affordable, safer, and provides performance close to fossil fuels (such as autonomy and power).
[0005] Organic cathode is the main candidate for producing batteries that meet energy storage needs. One advantage of these materials is that the synthesis temperature is significantly lower than the temperature of intercalation materials (Armand et al., Nature, 2008, 451, 652). In addition, they are composed of abundant elements and have excellent electrochemical properties (Le Gall et al., Journal of Power Sources, 2003, 316-320). On the other hand, their biggest drawback is related to the dissolution of active materials in electrolytes, which greatly affects the stability of batteries (Chen et al., ChemSusChem., 2008, 1, 348-355). Electrochemically active organic polymers can suppress or reduce the dissolution of active materials, so as to obtain materials with greater cyclicity (Zeng et al., ElectrochimicaActa, 2014, 447-454).
[0006] Elemental sulfur is also a candidate material for the production of high energy density batteries. Indeed, lithium sulfur (Li-S) batteries are very promising considering the advantages offered by this element, namely a high capacity of 1675 mAh / g and a large abundance, the latter attributed to the fact that sulfur is a byproduct of petroleum refineries (Hyun et al., ACS Energy Letters, 2016, 1, 566-572). However, Li-S batteries also have some disadvantages, including the production of polysulfides (Li2S) due to the reduction of sulfur during cycling. x, x = 4-8) dissolve. In addition, once the polysulfide dissolves, a phenomenon called "shuttle effect" occurs, which makes the lithium surface (anode) unstable. This phenomenon leads to reduced stability and low Coulombic efficiency (Zhou et al., J. Am. Chem. Soc. 2013, 135, 16736-16743).
[0007] One strategy to address this problem involves the encapsulation of sulfur particles. For example, Zhou et al. (J.Am.Chem.Soc.2013, 135, 16736-16743) coated sulfur with polyaniline (PANI) to fix the polysulfide in the shell. Sulfur encapsulation can improve the stability of the battery. However, the addition of this element limits the amount of sulfur in the active material to only 58% by weight, which means that 42% by weight of the material is composed of electrochemically inert materials, thereby reducing the charge density of the electrode material. Although this strategy can still achieve a coulombic efficiency of more than 97%, long-term cyclability is still limited.
[0008] Synthesis methods for carbon-sulfur composite materials have also been proposed. For example, Wang et al. (Journal of Power Sources, 2011, 7030-7034) have synthesized graphene-sulfur composites. This new material can not only improve the intrinsic conductivity, but also achieve an initial capacity almost equal to the theoretical value. However, the presence of graphene cannot suppress the phenomenon of polysulfide dissolution, and the capacity loss of the material is comparable to the capacity loss of sulfur itself.
[0009] In order to obtain sulfur-rich polymers, copolymerization of elemental sulfur with one or more organic monomers has also been explored. When sulfur is heated to above 159°C, ring opening of the (S8) ring occurs, resulting in diradicals that can undergo free radical polymerization. Chung et al. (Nature Chemistry, 2013, 5, 518-524) have developed a sulfur-rich copolymer for Li-S batteries. Elemental sulfur was copolymerized with different percentages of 1,3-diisopropenylbenzene (DIB) by inverse vulcanization. Copolymerization can produce a matrix that can limit the dissolution of polysulfides. Their electrochemical results show high coulombic efficiency as well as good capacity retention. However, as mentioned above, the organic monomers used are electrochemically inactive, which leads to the presence of inert substances and thus reduces the energy density.
[0010] Therefore, there is a need to develop new electrode materials that, for example, combine some of the advantages of the aforementioned materials while eliminating at least one of their disadvantages.
[0011] Overview
[0012] According to a first aspect, the present invention relates to a polymer of formula I:
[0013]
[0014] Wherein:
[0015] A is selected from unsaturated groups that allow electron delocalization, such as substituted or unsubstituted aryl and heteroaryl, and their fused or unfused polycyclic equivalents;
[0016] R is a substituted or unsubstituted organic linking group selected from straight-chain or branched C 2-6 alkylene, straight-chain or branched C 2-6 alkyleneoxy, straight-chain or branched C 2-6 alkylenediol, straight-chain or branched C 2-6 alkyleneoxyC 2-6 alkylene, straight-chain or branched poly(C 2-6 alkylenediol), C 6-12 arylene, C 3-12 cycloalkylene, C 5-12 heteroarylene and C 3-12 heterocycloalkylene;
[0017] m represents the average number of sulfur atoms inserted into the disulfide bonds of the polymer chain and cannot be 0, i.e., m > 0. For example, 0 < m ≤ 8, or 1 ≤ m ≤ 6, or 1 ≤ m ≤ 4; and
[0018] n represents the average number of units in the polymer. For example, n can range from 2 to 500 or from 5 to 300.
[0019] According to one embodiment, A is selected from phenyl, naphthyl, perylenyl, and biphenyl. For example, when A is phenyl, the polymer is of formula I(a):
[0020]
[0021] wherein R, m, and n are as defined herein.
[0022] According to another embodiment, R is selected from phenylene, ethylene, propylene, poly(ethylene glycol), poly(propylene glycol), and copolymers of ethylene glycol and propylene glycol.
[0023] Examples of the polymer are also illustrated by formula I(b):
[0024]
[0025] wherein m and n are as defined herein.
[0026] According to another aspect, the present invention relates to a compound of formula II:
[0027]
[0028] Wherein A and R are as defined herein, and m represents the number of sulfur atoms in the disulfide bond of the insertion compound. For example, m > 0, such as 0 < m ≤ 8, or 1 ≤ m ≤ 6, or 1 ≤ m ≤ 4.
[0029] An example of the compound is represented by formula II(a):
[0030]
[0031] Wherein R and m are as defined herein.
[0032] Another example of the compound is illustrated by formula II(b):
[0033]
[0034] Wherein m is as defined herein.
[0035] According to another aspect, the present invention relates to an electrode material comprising a polymer or a compound as defined herein. For example, the electrode material further comprises a conductive material, a binder, or a combination of both. The electrode material may also comprise free elemental sulfur (S x ).
[0036] According to one embodiment, the conductive material is selected from carbon black, Ketjen TM carbon, Shawinigan carbon, acetylene black, graphite, graphene, carbon fiber (such as carbon nanofiber (e.g., VGCF formed in the gas phase)), carbon nanotube, or a combination of at least two thereof.
[0037] According to one embodiment, the binder is a polymer binder of polyether type, fluorinated polymer type, or a water-soluble binder. According to one example, the polymer binder of polyether type is linear, branched, and / or crosslinked, and is based on polyethylene oxide (PEO), polypropylene oxide (PPO), or a combination of both (or EO / PO copolymer), and optionally contains crosslinkable units. According to another example, the fluorinated polymer binder is PVDF (polyvinylidene fluoride) or PTFE (polytetrafluoroethylene). Finally, examples of the water-soluble binder include SBR (styrene-butadiene rubber), NBR (acrylonitrile-butadiene rubber), HNBR (hydrogenated NBR), CHR (epichlorohydrin rubber), or ACM (acrylate rubber), optionally containing CMC (carboxymethyl cellulose).
[0038] According to another aspect, the present invention relates to a positive electrode comprising the electrode material as defined herein applied on a current collector.
[0039] According to another aspect, the present invention also relates to an electrolyte comprising a polymer as defined herein or a compound as defined herein. According to one embodiment, the electrolyte is a liquid electrolyte comprising a salt in a solvent. According to an alternative, the electrolyte is a gel electrolyte comprising a salt and an optional solvated polymer in a solvent. According to a second alternative, the electrolyte is a solid polymer electrolyte (SPE) comprising a salt in a solvated polymer. For example, the polymer as defined herein or the compound as defined herein is an additive. Alternatively, the solvated polymer of the SPE is a polymer as defined herein or a compound as defined herein. According to another embodiment, the salt is a lithium salt. According to one embodiment, the electrolyte further comprises elemental sulfur, a binder, an additive or a combination of at least two thereof.
[0040] Another aspect relates to an electrochemical cell comprising a cathode, an electrolyte and an anode, wherein the cathode comprises an electrode material as defined herein. According to an alternative embodiment, these electrochemical cells comprise a negative electrode, an electrolyte and a positive electrode as defined herein. According to an alternative embodiment, these electrochemical cells comprise a cathode, an anode and an electrolyte as defined herein. The present invention also relates to a lithium battery comprising such an electrochemical cell.
[0041] Finally, the invention relates to methods for producing the polymers and compounds defined herein, electrode materials, electrolyte materials, electrodes, electrolytes and electrochemical cells comprising them. The use of these electrochemical cells is also contemplated, in particular in portable devices, such as in mobile phones, cameras, tablets or laptops, in electric or hybrid vehicles or in renewable energy storage. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The results of capacity (mAh / g) and capacity retention percentage as a function of cycle number are given in (A) for battery 1 (reference), wherein battery 1 comprises polyimide disulfide, and the results of capacity (mAh / g) and capacity retention percentage as a function of cycle number are given in (B), wherein battery 2 comprises polyimide-co-polysulfide, wherein the polysulfide comprises 35 wt. % sulfur.
[0044] Figure 2 Shown are galvanostatic curves representing the capacity (mAh / g) versus voltage (V) results for Battery 2 comprising the copolymer shown in Example 1(c) at the first cycle at C / 10.
[0045] Figure 3 Galvanostatic curves are shown, which represent the capacity (mAh / g) as a function of voltage (V) for the first charge and discharge cycle of Battery 3 (dashed line), Battery 4 (thick solid line) and Battery 5 (thin solid line).
[0046] Figure 4 Galvanostatic curves are shown, which represent the capacity (mAh / g) as a function of voltage (V) for the first charge and discharge cycle of Battery 6 (dashed line) and Battery 7 (solid line).
[0047] Figure 5 (A) shows the cyclic voltammograms of cells 8 (dashed line) and 9 (solid line) containing the active material of Example 1(h), Figure 5 (B) shows a constant current curve, which represents the capacity (mAh / m) of the first charge and discharge cycle of batteries 8 and 9 as a function of voltage (V).
[0048] Figure 6 The infrared transmission spectra of the active electrode materials given in Example 1(b), (c), (d), the monomers used in the copolymerization, the imide copolymer without added sulfur, and elemental sulfur are shown.
[0049] Figure 7 Shown are the infrared transmission spectra of the active electrode materials given in Examples 1(f) and 1(g), the monomers used in the copolymerization, elemental sulfur, and the copolymer without added sulfur.
[0050] Figure 8 Shown are the infrared transmission spectra of the active material given in Example 1(h), the monomers used for copolymerization, elemental sulfur and the copolymer without added sulfur.
[0051] Fig. 9 The ionic conductivity (S cm) of the copolymer given in Example 1(c) is shown in FIG. -1 ) with temperature (K -1 ) results of changes.
[0052] Fig.10 The ionic conductivity (S cm) of the copolymer given in Example 1(d) is shown in FIG. -1 ) with temperature (K -1 ) results of changes.
[0053] Fig.11 The ionic conductivity (S cm) of the copolymer given in Example 1(g) is shown in FIG. -1 ) with temperature (K -1 ) results. The ionic conductivity values of the membrane as described in Example 5(c) are given in (A); the ionic conductivity values of the pressed powder form as described in Example 5(d) are given in (B).
[0054] Details
[0055] All technical and scientific terms used herein have the same definitions as commonly understood by one of ordinary skill in the art to which this technology relates. However, definitions of some of the terms and expressions used are provided below.
[0056] As used herein, the term "about" means approximately, in the region of, and near. When the term "about" is used in conjunction with a numerical value, it is, for example, 10% above and below the nominal value. The term can also take into account experimental errors such as measurement equipment or rounding.
[0057] When a range of values is mentioned in this application, the lower and upper limits of the range are always included in the definition unless otherwise indicated.
[0058] The chemical structures described herein are drawn according to standards in the art. Likewise, when a drawn atom, such as a carbon atom, appears to contain incomplete valences, one or more hydrogen atoms are assumed to satisfy the valences even if these valences are not explicitly drawn.
[0059] As used herein, the term "alkyl" or "alkylene" refers to a saturated hydrocarbon group having 1 to 16 carbon atoms, including straight or branched groups. Examples of alkyl groups include, but are not limited to, methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, isopropyl, tert-butyl, sec-butyl, isobutyl, etc. When the alkyl group is between two functional groups, the term alkylene may also be used, such as methylene, ethylene, propylene, etc. The term "C i -C ii Alkyl" and "C i -C ii "Alkylene" refers to an alkyl group or an alkylene group having a carbon number "i" to a number "ii", respectively.
[0060] As used herein, the term "aryl" or "arylene" refers to an aromatic group having 4n+2π (pi) electrons in a conjugated monocyclic or polycyclic system (fused or non-fused) having 6-20 ring atoms, wherein n is an integer from 1 to 3. The polycyclic system includes at least one aromatic ring. The group may be directly connected or connected through a C1-C3 alkyl group. Examples of aryl include, but are not limited to, phenyl, benzyl, phenethyl, 1-phenethyl, tolyl, naphthyl, biphenyl, terphenyl, indenyl, benzocyclooctenyl, benzocycloheptenyl, azulenyl, acenaphthenyl, fluorenyl, phenanthrenyl, anthracenyl, perylenyl, etc. When the aryl group is located between two functional groups, the term arylene may also be used. The term arylene includes substituted or unsubstituted groups. For example, the term "C6-C n "Aryl" refers to aromatic groups having from 6 to the indicated "n" number of carbon atoms in the ring structure.
[0061] When combined with a group, the term "substituted" refers to a group in which at least one hydrogen atom has been replaced by a suitable substituent. Non-limiting examples of substituents include cyano, halogen (i.e., F, Cl, Br or I), amide, nitro, trifluoromethyl, lower alkyl, cycloalkyl, heterocycloalkyl, aryl, heteroaryl, lower alkoxy, aryloxy, benzyloxy, benzyl, alkoxycarbonyl, sulfonyl, sulfonate, silane, siloxane, phosphonic acid, phosphinic acid, etc. If permitted, these substituents may also be substituted, for example, if the group contains alkyl, alkoxy, aryl, etc.
[0062] The present invention relates to the copolymerization of elemental sulfur with organic monomers or to the reaction of sulfur with compounds containing disulfide bonds. For example, the present application includes a polymer that is the result of the copolymerization of sulfur with an electrochemically active polyimide. Alternatively, sulfur is reacted with diimide disulfide to obtain a compound containing electrochemically active sulfide segments and organic segments. These compounds and polymers can not only improve the electrochemical performance of sulfur by reducing or eliminating dissolution problems, but also contribute to the capacity due to the presence of organic segments that are also active in redox reactions. Therefore, the electrode material containing the polymer or compound defined herein can be characterized as a hybrid organic sulfur positive electrode material.
[0063] For example, the polymer is composed of electrochemically active polyimide segments and polyimide segments of the form -S-(S) m -S- (where m ≥ 1) of the polysulfide chain segments. An example of the polymer is represented by formula I:
[0064]
[0065] in:
[0066] A is selected from unsaturated groups that allow electron delocalization, such as substituted or unsubstituted aryl and heteroaryl groups, and fused or unfused polycyclic equivalents thereof;
[0067] R is a substituted or unsubstituted organic linking group selected from a linear or branched C 2-6 Alkylene, linear or branched C 2-6 Alkyleneoxy, linear or branched, C 2-6 Alkylene glycols, linear or branched, C 2-6 Alkyleneoxy C 2-6 Alkylene, linear or branched poly(C 2-6 Alkylene glycol), C 6-12 Arylene, C 3-12 Cycloalkylene, C 5-12 Heteroarylene and C 3-12 heterocycloalkylene;
[0068] m represents the average number of sulfur atoms inserted into the disulfide bonds of the polymer chain, and cannot be 0, i.e., m > 0. For example, 0 < m ≤ 8, or 1 ≤ m ≤ 6, or 1 ≤ m ≤ 4; and
[0069] n represents the average number of units in the polymer. For example, n can range from 2 to 500 or from 5 to 300.
[0070] According to one example, A can be selected from phenyl, naphthyl, perylenyl, and biphenyl.
[0071] For example, A is phenyl and the polymer is of formula I(a):
[0072]
[0073] where R, m, and n are as defined herein.
[0074] According to another example, R can be selected from the groups phenylene, ethylene, propylene, poly(ethylene glycol), poly(propylene glycol), and copolymers of ethylene glycol and propylene glycol.
[0075] For example, A and R are phenyl, and the molecular formula of the polymer is I(b) or I(c):
[0076]
[0077] where m and n are as defined herein.
[0078] According to another example, the active material is a compound of formula II:
[0079]
[0080]
[0081] where A and R are as defined herein, and m represents the average number of sulfur atoms inserted into the disulfide bonds of the compound. For example, m > 0, for example 0 < m ≤ 8, or 1 ≤ m ≤ 6, or 1 ≤ m ≤ 4.
[0082] For example, A is benzene and the polymer is of formula II(a):
[0083]
[0084] where R and m are as defined herein.
[0085] For example, R is phenylene and the polymer is of formula II(b):
[0086]
[0087] where m is as defined above.
[0088] The present application also describes a method for synthesizing a polymer as defined herein and comprising an organosulfide hybrid, comprising the steps of polymerization and sulfurization by reaction with elemental sulfur, these steps being performed in any order. For example, the method comprises the following steps:
[0089] a) polymerizing by polycondensation between a dianhydride and a diamine disulfide to form an electrochemically active polyimide; and
[0090] b) Insertion of polysulfide segments (-(S)) by copolymerization of electrochemically active polyimide and elemental sulfur S8 m -form; where m≥1).
[0091] According to one example, the copolymer organic segment is synthesized by polycondensation between pyromellitic dianhydride (1) and 4-aminophenyl disulfide (2) to form polyimide (3). For example, the polycondensation reaction is carried out at a temperature of about 150° C. The copolymer can be prepared by a polymerization method as shown in Scheme 1:
[0092]
[0093] According to one embodiment, the polysulfide segment (in the form of -(S) m -; wherein m≥1) is inserted into the disulfide bond. The electrochemically active polyimide comprising disulfide bonds and elemental sulfur S8 can then be inserted by heating at a temperature of 150°C or higher, or 185°C or higher, or between 160°C and 200°C. The heating step allows the elemental sulfur S8 ring to be opened to insert the polysulfide segment (in the form of -(S) m -; wherein m≥1) is inserted into the disulfide bond and forms a polysulfide. The insertion of the polysulfide segment can be carried out according to the method shown in Scheme 2, wherein the polysulfide segment (in the form of -(S) m -; wherein m≥1) is inserted at 185°C on the disulfide bonds of the polyimide (3) to obtain a polyimide-co-polysulfide (4):
[0094]
[0095] Alternatively, the present application describes a method for synthesizing a polymer as defined herein and comprising an organosulfide hybrid, the method comprising the following steps:
[0096] a) By inserting polysulfide segments (in the form of -(S) m -; wherein m≥1) synthesizes amino-sulfur comonomers by polymerization of diamine disulfide and elemental sulfur S8; and
[0097] b) Polycondensation of the amino-sulfur comonomer and the dianhydride to form a polyimide.
[0098] According to one embodiment, the polysulfide segment (in the form of -(S) m -; wherein m≥1) is inserted into the disulfide bonds of the diamine disulfide. The insertion can be carried out by heating the elemental sulfur S8 and the diamine disulfide having disulfide bonds at a temperature of 150°C or higher, or 185°C or higher, or between 160°C and 200°C. The heating step allows the elemental sulfur S8 ring to open to insert the polysulfide segment in the disulfide bond, thereby forming the polysulfide. The insertion of the polysulfide segment can be carried out by the method shown in Scheme 3, wherein the insertion of the polysulfide segment is carried out at 185°C in the disulfide bond of 4-aminophenyl disulfide (2) to obtain the amino-sulfur comonomer (3):
[0099]
[0100] According to one example, polymerization is then carried out by a polycondensation reaction between the amino-sulfur comonomer (3) and the pyromellitic dianhydride (4) to form a polyimide-co-polysulfide (5). The polycondensation reaction can be carried out, for example, at a temperature of about 150° C. The polymer can be prepared by a polymerization method as shown in Scheme 4:
[0101]
[0102] wherein the values of m and n depend on the mass percentage of sulfur in the reaction mixture. The mass percentage of sulfur in the copolymer may vary between 0.1% and 99.9%, for example between 5% and 95%. The polymer may also contain a certain residual amount of free elemental sulfur that is not incorporated into the disulfide bonds, especially when a large amount of sulfur is included in the insertion step.
[0103] The present application also proposes a positive electrode material comprising a polymer or compound as defined herein as an electrochemically active material. According to one example, the positive electrode material may further include a conductive material, a binder or a combination thereof. The electrode material may also include free elemental sulfur (S x ).
[0104] Non-limiting examples of conductive materials may include carbon sources such as carbon black, Ketjen TM Carbon, Shawinigan carbon, acetylene black, graphite, graphene, carbon fiber (e.g., carbon nanofiber, such as VGCF formed in the gas phase), carbon nanotube or a combination of at least two thereof. For example, the conductive material is VGCF and Ketjen TM Carbon black combination.
[0105] Non-limiting examples of binders include linear, branched and / or cross-linked polyether polymers, which may be based on polyethylene oxide (PEO), polypropylene oxide (PPO) or a combination of the two (or EO / PO copolymers), and optionally include cross-linkable units; fluorinated polymers, such as polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); or water-soluble binders, such as styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), hydrogenated NBR (HNBR), epichlorohydrin rubber (CHR) or acrylate rubber (ACM), and optionally include carboxymethyl cellulose (CMC). For example, the binder is PVDF, and when mixed with the other components of the positive electrode material, it is dissolved in N-methyl-2-pyrrolidone (NMP) to disperse, and then the solvent is removed.
[0106] According to one example, the positive electrode material can be applied to a current collector (e.g., aluminum, copper). Alternatively, the positive electrode can be free-standing. For example, the current collector is aluminum.
[0107] The present application also proposes an electrochemical cell comprising at least a positive electrode material as defined herein, a negative electrode and an electrolyte. The electrolyte is then selected so as to be compatible with the different components of the battery. Any type of electrolyte may be considered, such as a liquid, gel or solid electrolyte.
[0108] The present application also proposes an electrolyte comprising a polymer as defined herein or a compound as defined herein.
[0109] According to one example, the electrolyte is a liquid electrolyte comprising a salt in a solvent. According to an alternative, the electrolyte is a gel electrolyte comprising a salt in a solvent and optionally a solvating polymer. According to another alternative, the electrolyte is a solid polymer electrolyte (SPE) comprising a salt in a solvating polymer.
[0110] Compatible electrolytes typically include at least one lithium salt, such as lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), 2-trifluoromethyl-4,5-dicyanoimidazole lithium (LiTDI), 4,5-dicyano-1,2,3-triazole lithium (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium nitrate (LiNO3), lithium chloride (LiCl), lithium bromide (LiBr), lithium fluoride (LiF), and compositions thereof dissolved in non-aqueous solvents (organic) or solvated polymers. For example, the electrolyte is LiTFSI dissolved in dimethoxyethane (DME) and 1,3-dioxolane (DOL) (DME / DOL), and includes lithium nitrate (1%, LiNO3).
[0111] According to another example, the electrolyte may further include elemental sulfur, an electrolyte binder, a separator, an additive, or a combination of at least two thereof.
[0112] For example, the electrolyte binder is PVDF (polyvinylidene fluoride). For example, the electrolyte contains 0 wt % to 25 wt %, particularly 0 wt % to 20 wt %, more particularly 5 wt % to 15 wt %, even more particularly 7 wt % to 13 wt %, ideally 10 wt % of the electrolyte binder, including upper and lower limits.
[0113] Non-limiting examples of the separator may include polyethylene (PE), polypropylene (PP), cellulose, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), and polypropylene-polyethylene-polypropylene (PP / PE / PP) films.
[0114] According to another example, the electrolyte is a solid polymer electrolyte (SPE) comprising a salt defined herein in a solvated polymer, wherein the solvated polymer is a polymer defined herein. For example, the SPE comprises 60% to 95% by weight, particularly 65% to 90% by weight, more particularly 70% to 85% by weight, even more particularly 75% to 85% by weight, and ideally 80% by weight of a polymer defined herein, including upper and lower limits. For example, the SPE comprises 5% to 40% by weight, particularly 10% to 35% by weight, more particularly 15% to 30% by weight, more particularly 15% to 25% by weight, and ideally 20% by weight of a salt, including upper and lower limits.
[0115] The present application also proposes an electrochemical cell comprising a cathode, an anode and an electrolyte as defined herein. The present application also contemplates an electrochemical cell comprising a cathode, an anode and an electrolyte, wherein the electrolyte and the cathode are as defined herein.
[0116] According to another aspect, the electrochemical cell of the present application is included in a lithium battery. For example, the lithium battery is a lithium sulfur battery.
[0117] According to another aspect, the electrochemical cell of the present application is used in a portable device, such as a mobile phone, a camera, a tablet or a laptop computer, an electric or hybrid vehicle or in renewable energy storage. Example
[0118] The following examples are illustrative and should not be construed to further limit the scope of the invention described.
[0119] Example 1 - Synthesis of organic sulfur hybrid active electrode materials
[0120] a) Copolymerization of pyromellitic dianhydride, 4-aminophenyl disulfide and sulfur (5% by weight)
[0121] The synthesis of the electrode material was carried out in a 25 mL flask equipped with a magnetic bar. The active electrode material was prepared by combining 0.085 g of elemental sulfur S8 (0.33 mmol) and 0.745 g of 4-aminophenyl disulfide (3 mmol). The flask was then sealed and placed under an inert gas (N2) flow. Once the atmosphere of the flask was purged, the mixture was heated to a temperature of 185°C for about 30 minutes under constant stirring at 500 rpm until a uniform liquid was obtained. The mixture was then cooled to a temperature of 150°C and the sealing cap was then removed to add 0.654 g of pyromellitic dianhydride (3 mmol) pre-dissolved in an organic solvent N,N-dimethylformamide (DMF). The flask containing the mixture was then capped and kept at a temperature of 150°C for 26 hours under stirring (500 rpm). The mixture was then cooled. The resulting solid was recovered, washed with tetrahydrofuran (THF) and dried under vacuum to sublime the unreacted sulfur. Finally, the percentage of sulfur in the resulting active electrode material (polymer) was determined by elemental analysis. The active electrode material of this example contained 5% sulfur.
[0122] b) Copolymerization of pyromellitic dianhydride, 4-aminophenyl disulfide and sulfur (25% by weight)
[0123] The synthesis of the active electrode material was carried out according to the method described in Example 1(a). The mass of elemental sulfur S8 and 4-aminophenyl disulfide used to synthesize the amino-sulfur comonomer was 0.309 g (1.206 mmol) and 0.447 g (1.8 mmol), respectively, and the mass of pyromellitic dianhydride used for polycondensation was 0.393 g (1.8 mmol). The active electrode material thus prepared contained 25% by weight of sulfur as determined by elemental analysis.
[0124] c) Copolymerization of pyromellitic dianhydride, 4-aminophenyl disulfide and sulfur (35% by weight)
[0125] The synthesis of the active electrode material was carried out according to the method described in Example 1(a). The masses of elemental sulfur S8 and 4-aminophenyl disulfide used to synthesize the amino-sulfur comonomer were 1.033 g (4.026 mmol) and 1 g (4.026 mmol), respectively, and the mass of pyromellitic dianhydride used for polycondensation was 0.878 g (4.026 mmol). The active electrode material thus prepared contained 35% by weight of sulfur as determined by elemental analysis.
[0126] d) Copolymerization of pyromellitic dianhydride, 4-aminophenyl disulfide and sulfur (63 wt%)
[0127] The synthesis of the active electrode material was carried out according to the method described in Example 1(a). The masses of elemental sulfur S8 and 4-aminophenyl disulfide used to synthesize the amino-sulfur comonomer were 2.463 g (9.6 mmol) and 0.397 g (1.6 mmol), respectively, and the mass of pyromellitic dianhydride used for polycondensation was 0.349 g (1.6 mmol). The active electrode material thus obtained contained 63% by weight of sulfur as determined by elemental analysis.
[0128] e) Copolymerization of pyromellitic dianhydride, 4-aminophenyl disulfide and sulfur (95% by weight)
[0129] The synthesis of the active electrode material was carried out according to the method described in Example 1(a). The masses of elemental sulfur S8 and 4-aminophenyl disulfide used to synthesize the amino-sulfur comonomer were 8.978 g (35 mmol) and 0.248 g (1 mmol), respectively, and the mass of pyromellitic dianhydride used for polycondensation was 0.218 g (1 mmol). The active electrode material thus prepared contained 95% by weight of sulfur as determined by elemental analysis.
[0130] f) Copolymerization of 1,4,5,8-naphthalenetetracarboxylic dianhydride, 4-aminophenyl disulfide and sulfur (20% by weight)
[0131]
[0132] The synthesis of the electrode material was carried out in a 25 mL flask equipped with a magnetic bar. The active electrode material was prepared by mixing 0.923 g of elemental sulfur S8 (3.6 mmol) and 0.447 g of 4-aminophenyl disulfide (1.8 mmol). The flask was then sealed and placed under an inert gas (N2) flow. Once the atmosphere of the flask was purged, the mixture was heated to a temperature of 185 ° C for about 30 minutes under constant stirring at 500 rpm until a uniform liquid was obtained. The mixture was then cooled to a temperature of 150 ° C, and the sealing cap was then removed to add 0.483 g of 1,4,5,8-naphthalenetetracarboxylic dianhydride (1.8 mmol) pre-dissolved in an organic solvent N,N-dimethylformamide (DMF). The flask containing the mixture was then covered and kept at a temperature of 150 ° C for 26 hours under stirring (500 rpm). The mixture was then cooled. The resulting solid was collected, washed with tetrahydrofuran (THF) and dried under vacuum to sublimate the unreacted sulfur. Finally, the percentage of sulfur in the prepared active electrode material (polymer) was determined by elemental analysis. The active electrode material of this example contained 20% sulfur.
[0133] g) Copolymer of 1,4,5,8-naphthalenetetracarboxylic dianhydride, 4-aminophenyl disulfide and sulfur (30 wt%)
[0134] The synthesis of the active electrode material was carried out according to the method described in Example 1(f). The masses of elemental sulfur S8 and 4-aminophenyl disulfide used to synthesize the amino-sulfur comonomer were 2.052 g (8 mmol) and 1.987 g (8 mmol), respectively, and the mass of 1,4,5,8-naphthalenetetracarboxylic dianhydride used for polycondensation was 2.145 g (8 mmol). The active electrode material thus prepared contained 30% by weight of sulfur as determined by elemental analysis.
[0135] h) Copolymerization of pyromellitic dianhydride and cystamine by polycondensation followed by insertion of sulfur (20 wt%)
[0136] The synthesis of the copolymer was carried out in a 100 mL flask equipped with a magnetic bar. The material was prepared by combining 7.614 g of cystamine dihydrochloride (0.5 mol) and 10.91 g of pyromellitic anhydride (0.5 mol). The mixture was then heated to a temperature of 150 ° C for 26 hours under stirring (500 rpm). The mixture was then cooled. The resulting solid was recovered and washed with tetrahydrofuran (THF). Then 1.204 g of the copolymer was dispersed in NMP and 1.856 g of elemental sulfur S8 (50 wt %) was added. The flask was then sealed and placed under an inert gas (N2) flow. After purging the atmosphere in the flask, the mixture was heated to 185 ° C for about 20 hours under constant stirring at 500 rpm. The mixture was then cooled. The resulting solid was recovered, washed with tetrahydrofuran (THF) and dried under vacuum to sublimate the unreacted sulfur. Finally, the sulfur percentage in the produced active electrode material (polymer) was determined by elemental analysis. The active electrode material of this example contains 20% sulfur.
[0137] Example 2 - Preparation of electrochemical cell
[0138] a) Cathode
[0139] The cathode material is composed of 60 wt% of a hybrid organic sulfide electrode material (i.e., polyimide-co-polysulfide or polyimide disulfide (reference) of Example 1), 30 wt% of a conductive carbon (15% VGCF and 15% Ketjen TM 600 carbon) and 10% by weight of a binder (polyvinylidene fluoride (PVDF) dissolved in N-methyl-2-pyrrolidone (NMP). The current collector is aluminum. After spreading, the solvent is evaporated.
[0140] b) Electrolytes
[0141] The electrolyte consisted of 1 M lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) and lithium nitrate (1%, LiNO3) dissolved in a mixture of dimethoxyethane (DME) and 1,3-dioxolane (DME / DOL).
[0142] c) Anode
[0143] The anode consists of metallic lithium in thin film form.
[0144] d) Electrochemical cells
[0145] Therefore, prepare a battery with the following elements:
[0146] Lithium / electrolyte / cathode / aluminum
[0147] Battery 1
[0148] Cell 1 included a reference cathode comprising the disulfide polyimide presented in Example 2(a), the electrolyte presented in Example 2(b), and an anode composed of metallic lithium presented in Example 2(c).
[0149] Battery 2
[0150] Battery 2 comprises the cathode presented in Example 2(a) comprising the electrode material of Example 1(c), the electrolyte presented in Example 2(b) and the anode composed of metallic lithium presented in Example 2(c).
[0151] Battery 3
[0152] Battery 3 comprises the cathode presented in Example 2(a) comprising the electrode material of Example 1(d), the electrolyte presented in Example 2(b) and the anode composed of metallic lithium presented in Example 2(c).
[0153] Battery 4
[0154] Battery 4 comprises the cathode presented in Example 2(a) comprising the electrode material of Example 1(e), the electrolyte presented in Example 2(b) and the anode composed of metallic lithium presented in Example 2(c).
[0155] Battery 5
[0156] Battery 5 includes the cathode presented in Example 2(a) comprising the electrode material of Example 1(b), the electrolyte presented in Example 2(b) and the anode composed of metallic lithium presented in Example 2(c).
[0157] Battery 6
[0158] Battery 6 comprises the cathode presented in Example 2(a) comprising the electrode material of Example 1(f), the electrolyte presented in Example 2(b) and the anode composed of metallic lithium presented in Example 2(c).
[0159] Battery 7
[0160] Battery 7 comprises the cathode presented in Example 2(a) comprising the electrode material of Example 1(g), the electrolyte presented in Example 2(b) and the anode composed of metallic lithium presented in Example 2(c).
[0161] Battery 8
[0162] Battery 8 comprises the cathode presented in Example 2(a) comprising the electrode material of Example 1(h) (without added sulfur), the electrolyte presented in Example 2(b) and the anode (C) composed of metallic lithium presented in Example 2(c).
[0163] Battery 9
[0164] Battery 9 includes the cathode presented in Example 2(a) comprising the electrode material containing 20 wt% sulfur of Example 1(a), the electrolyte presented in Example 2(b) and the anode composed of metallic lithium presented in Example 2(c).
[0165] Example 3 - Electrochemical Properties
[0166] Electrochemical measurements were performed on the electrochemical cell of Example 2(d). Figure 1 As shown, the presence of sulfur inserted into disulfide bonds allows obtaining better performing materials with improved capacity and cyclability. Figure 1 (A) and 1 (B) show the capacity and capacity retention results as a function of the number of cycles for Cell 1 (reference) and Cell 2, respectively. Indeed, by comparing the results, a significant improvement in the capacity and capacity retention percentage can be observed for Cell 2 compared to Cell 1.
[0167] Figure 2 The capacity versus voltage results for the first cycle at C / 10 in Cell 2 are given, where the contribution of the polymer to the capacity of the new material can be observed by the presence of a plateau at about 2.2 V. Cell 2 achieves 290 mAh g at C / 10 -1 The first discharge capacity at C / 2 achieved a capacity retention percentage of 65% after 100 cycles.
[0168] Figure 3 The first charge-discharge curves at C / 10 for cells 3 to 5 are given, where the initial capacity depends on the properties of the active material. The capacities obtained for cells 3, 4, and 5 are 407 mAh g -1 , 570mAh g -1 and 277mAh g -1 .
[0169] Figure 4 The capacity variation with voltage of the first cycle at C / 10 for cells 6 and 7 is given, where the contribution of sulfur to the capacity of the new material can be observed by the presence of a plateau at around 2.05 V. Cell 6 achieved 305 mAh g at C / 10. -1 The first discharge capacity was 443 mAh g at C / 10 and a capacity retention of 91% was obtained after 50 cycles at C / 2. -1 , after 50 cycles, the capacity retention percentage is 75%.
[0170] Figure 5 (a) shows the cyclic voltammograms of cells 8 and 9. It can be seen that the effect of sulfur addition on the intensity of the oxidation and reduction peaks. In addition, as Figure 5 As shown in (b), when sulfur is added, the capacity increases. Battery 8 achieved 138 mAh g at C / 10. -1 The initial discharge capacity was 195 mAh g at C / 10, and a capacity retention of 37% was obtained after 100 cycles at C / 2. -1 , the capacity retention percentage after 100 cycles is 50%.
[0171] Example 4 - Characterization and determination of material composition
[0172] The composition of the material provided in Example 1 was determined using transmission infrared spectroscopy. Figure 6 The infrared transmission spectra of the active electrode materials shown in Example 1(b), (c), (d) are given, as well as the spectra of the monomers used during copolymerization, the spectrum of the imide copolymer without added sulfur, and the spectrum of elemental sulfur.
[0173] Figure 7 The infrared transmission spectra of the active electrode materials provided in Examples 1(f) and 1(g) are shown, as well as the spectra of the monomers used in the copolymerization, elemental sulfur, and sulfur-free copolymers.
[0174] Figure 8 The infrared transmission spectrum of the active electrode material provided in Example 1(h) is shown, as well as the spectrum of the monomer used for copolymerization, elemental sulfur and the copolymer without added sulfur.
[0175] Example 5 - Ionic Conductivity
[0176] a) Measuring the ionic conductivity of the material provided in Example 1(c)
[0177] The ionic conductivity results were obtained for the copolymer provided in Example 1(c). To this end, the copolymer provided in Example 1(c) was mixed with a lithium salt (LiTFSI) and with a binder (PVDF) in an organic solvent (NMP). The homogeneous dispersion was spread on a stainless steel foil with a thickness of 27 μm. The film was then dried at a temperature of 120° C. for 16 hours. The NMP was evaporated and the ratio (copolymer: LiTFSI: PVDF) obtained was 70:20:10 (mass percentage).
[0178] The resulting membrane was then placed between two stainless steel electrodes and assembled into a button cell to measure ionic conductivity. Electrochemical impedance spectroscopy was performed between 800 kHz and 100 Hz at various temperatures (25°C, 40°C, 60°C, and 80°C).
[0179] Fig. 9 The graph in Figure 2 shows the change in conductivity values with temperature. A maximum value of 3.06×10 -6 S.cm -1 .
[0180] b) Measuring the ionic conductivity of the material provided in Example 1(d)
[0181] Using the method and ratio shown in Example 5(a), the conductivity of the sulfur-containing copolymer provided in Example 1(d) was measured as a function of temperature. The ionic conductivity results are shown in Fig.10 The maximum value of 1.12 x 10 - 8 S.cm -1 .
[0182] c) Measuring the ionic conductivity of the material provided in Example 1(g)
[0183] Using the method and ratio shown in Example 5(a), the conductivity of the sulfur-containing copolymer provided in Example 1(g) was measured as a function of temperature. The results are shown in Fig.11 (A). The maximum value of 6.43×10 -9 S.cm -1 .
[0184] d) Measuring the ionic conductivity of the material provided in Example 1(g)
[0185] For the sulfur-containing copolymer provided in Example 1(g), the ionic conductivity was measured a second time. To this end, the sulfur-containing copolymer provided in Example 1(g) was mixed with 20 wt % of a lithium salt (LiTFSI). The solid mixture was pressed between two stainless steel electrodes at a temperature of 150° C. for 30 minutes. The electrochemical impedance spectroscopy was then measured between 800 kHz and 100 Hz at various temperatures (25° C., 40° C., 60° C. and 80° C.). The results are shown in Fig.11 (B) The maximum ionic conductivity at 40°C is 1.1×10 -5 S.cm -1 .
[0186] Various modifications may be made to one or other of the above-described embodiments without departing from the scope of the invention.For all purposes, any reference, patent or scientific literature document cited in this application is hereby incorporated by reference in its entirety.
Claims
1. A polymer of formula I: Wherein: A is an unsaturated group that allows electron delocalization, selected from substituted or unsubstituted aryl groups having 6 - 20 ring atoms in a monocyclic system or a fused or non-fused polycyclic system; R is selected from substituted or unsubstituted straight or branched chain C 2-6 Alkylene, substituted or unsubstituted straight or branched chain C 2-6 Alkyleneoxy, substituted or unsubstituted straight-chain or branched C 2-6 Alkylene glycols, substituted or unsubstituted, straight or branched chain C 2-6 Alkyleneoxy C 2-6 Alkylene, substituted or unsubstituted linear or branched poly (C 2-6 Alkylene glycol), substituted or unsubstituted C 6-12 Arylene and substituted or unsubstituted C 3-12 a cycloalkylene organic linking group; m represents the average number of sulfur atoms inserted into the disulfide bonds of the polymer chain, and 0 < m ≤ 8; and n represents the average number of units in the polymer and is in the range of 2 to 500, where the weight percentage of sulfur in the polymer is between 0.1% and 99.9%, and where when the aryl group, alkylene group, alkyleneoxy group, alkylene diol, alkyleneoxyalkylene group, poly(alkylene diol), arylene group or cycloalkylene group is substituted, it is substituted with substituents selected from halogen, trifluoromethyl and lower alkyl groups.
2. The polymer according to claim 1, wherein m is 1 ≤ m ≤ 6.
3. The polymer according to claim 1 or 2, wherein A is selected from phenyl, naphthyl, perylenyl and biphenyl.
4. The polymer according to claim 1 or 2, wherein the polymer has formula I(a): Wherein R, m and n are as defined in claim 1 or 2.
5. The polymer according to claim 1 or 2, wherein R is selected from phenylene, ethylene, propylene, poly(ethylene glycol), poly(propylene glycol), and copolymers of ethylene glycol and propylene glycol.
6. The polymer according to claim 1 or 2, wherein the polymer has formula I(b): Wherein m and n are as defined in claim 1 or 2.
7. The polymer according to claim 1, wherein n is in the range of 5 to 300.
8. The polymer according to claim 1, wherein m is 1 ≤ m ≤ 4.
9. A compound of formula II: Wherein: A is an unsaturated group that allows electron delocalization, selected from substituted or unsubstituted aryl groups having 6 - 20 ring atoms in a monocyclic system or a fused or non-fused polycyclic system; R is selected from unsubstituted straight or branched C 2-6 Alkylene, substituted or unsubstituted straight or branched chain C 2-6 Alkyleneoxy, substituted or unsubstituted straight-chain or branched C 2-6 Alkylene glycols, substituted or unsubstituted, straight or branched chain C 2-6 Alkyleneoxy C 2-6 Alkylene, substituted or unsubstituted linear or branched poly (C 2-6 Alkylene glycol), substituted or unsubstituted C 6-12 Arylene and substituted or unsubstituted C 3-12 a cycloalkylene organic linking group; and m represents the number of sulfur atoms inserted into the disulfide bond of the compound, and 0 < m ≤ 8, where the weight percentage of sulfur in the compound is between 0.1% and 99.9%, and where when the aryl group, alkylene group, alkyleneoxy group, alkylene diol, alkyleneoxyalkylene group, poly(alkylene diol), arylene group or cycloalkylene group is substituted, it is substituted with substituents selected from halogen, trifluoromethyl and lower alkyl groups.
10. The compound according to claim 9, wherein m is 1 ≤ m ≤ 6.
11. The compound according to claim 9, wherein m is 1 ≤ m ≤ 4.
12. The compound according to claim 9 or 10, wherein R is selected from phenylene, ethylene, propylene, poly(ethylene glycol), poly(propylene glycol), and copolymers of ethylene glycol and propylene glycol.
13. The compound according to claim 9 or 10, wherein A is selected from phenyl, naphthyl, perylenyl and biphenyl.
14. The compound according to claim 9 or 10, wherein the compound has formula II(a): Wherein R and m are as defined in claim 9 or 10.
15. The compound according to claim 9 or 10, wherein the compound has formula II(b): Wherein m is as defined in claim 9 or 10.
16. An electrode material comprising the polymer according to any one of claims 1 to 8 or the compound according to any one of claims 9 to 15.
17. The electrode material of claim 16, further comprising elemental sulfur.
18. The electrode material according to claim 16 or 17, further comprising a conductive material, a binder or a combination of the two.
19. The electrode material according to claim 18, wherein the conductive material is selected from carbon black, graphite, graphene, carbon fiber and carbon nanotube, or a combination of at least two thereof.
20. The electrode material according to claim 19, wherein the carbon black is selected from Ketjen TM carbon, Shawinigan carbon, and acetylene black.
21. The electrode material according to claim 19, wherein the carbon fiber is a carbon nanofiber.
22. The electrode material according to claim 21, wherein the carbon nanofibers are formed in a gas phase.
23. The electrode material according to claim 18, wherein the binder is a polyether type polymer binder, a fluorinated polymer or a water-soluble binder.
24. Electrode material according to claim 23, wherein the polymer binder of the polyether type is linear, branched and / or crosslinked and is based on polyethylene oxide (PEO), polypropylene oxide (PPO), a mixture of the two, or an EO / PO copolymer, and optionally contains crosslinkable units.
25. The electrode material according to claim 23, wherein the fluorinated polymer binder is PVDF (polyvinylidene fluoride) or PTFE (polytetrafluoroethylene).
26. The electrode material according to claim 23, wherein the water-soluble binder is styrene-butadiene rubber, acrylonitrile-butadiene rubber, hydrogenated acrylonitrile-butadiene rubber, epichlorohydrin rubber or acrylate rubber, optionally containing carboxymethyl cellulose.
27. A positive electrode comprising an electrode material according to any one of claims 16 to 26 applied to a current collector.
28. An electrolyte comprising the polymer of any one of claims 1 to 8 or the compound of any one of claims 9 to 15.
29. The electrolyte of claim 28, wherein the electrolyte is a liquid electrolyte comprising a salt in a solvent.
30. The electrolyte of claim 28, wherein the electrolyte is a gel electrolyte comprising a salt and optionally a solvating polymer in a solvent.
31. An electrolyte according to claim 29 or 30, wherein the solvent is a polar aprotic solvent selected from ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), γ-butyrolactone (γ-BL), vinylene carbonate (VC), methyl butyrate (MB), γ-valerolactone (γ-VL), 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), 2-methyltetrahydrofuran, dimethyl sulfoxide, formamide, acetamide, dimethylformamide, dioxolane, acetonitrile, propionitrile, nitromethane, ethyl monoglyme, trimethoxymethane, sulfolane, methyl sulfolane, tetrahydrofuran and mixtures thereof.
32. The electrolyte according to claim 28, wherein the electrolyte is a solid polymer electrolyte (SPE) comprising a salt solvated in a polymer.
33. The electrolyte according to claim 28, wherein the polymer or the compound is an additive.
34. The electrolyte according to claim 32, wherein the solvated polymer is a polymer of formula I: Where: A is an unsaturated group allowing electron delocalization, selected from substituted or unsubstituted aryl groups having 6 - 20 ring atoms in a monocyclic system or a fused or non-fused polycyclic system; R is selected from substituted or unsubstituted straight or branched chain C 2-6 Alkylene, substituted or unsubstituted straight or branched chain C 2-6 Alkyleneoxy, substituted or unsubstituted straight-chain or branched C 2-6 Alkylene glycols, substituted or unsubstituted, straight or branched chain C 2-6 Alkyleneoxy C 2-6 Alkylene, substituted or unsubstituted linear or branched poly (C 2-6 Alkylene glycol), substituted or unsubstituted C 6-12 Arylene and substituted or unsubstituted C 3-12 a cycloalkylene organic linking group; m represents the average number of sulfur atoms inserted into the disulfide bonds of the polymer chain, and 0 < m ≤ 8; and n represents the average number of units in the polymer and ranges from 2 to 500, where the weight percentage of sulfur in the polymer is between 0.1% and 99.9%, and where when the aryl, alkylene, alkyleneoxy, alkylene diol, alkyleneoxyalkylene, poly(alkylene diol), arylene or cycloalkylene is substituted, it is substituted with substituents selected from halogen, trifluoromethyl and lower alkyl.
35. The electrolyte according to claim 28, wherein the electrolyte further comprises elemental sulfur.
36. The electrolyte according to any one of claims 29, 30 or 32, wherein the salt is a lithium salt.
37. The electrolyte according to claim 36, wherein the salt is selected from lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(fluorosulfonyl)imide (LiFSI), lithium 2-trifluoromethyl-4,5-dicyanoimidazole (LiTDI), lithium 4,5-dicyano-1,2,3-triazole (LiDCTA), lithium bis(pentafluoroethylsulfonyl)imide (LiBETI), lithium tetrafluoroborate (LiBF4), lithium bis(oxalato)borate (LiBOB), lithium nitrate (LiNO3), lithium chloride (LiCl), lithium bromide (LiBr), lithium fluoride (LiF), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiSO3CF3) (LiTf), lithium fluoroalkyl phosphate Li[PF3(CF2CF3)3] (LiFAP), lithium tetra(trifluoroacetoxy)borate Li[B(OCOCF3)4] (LiTFAB), lithium bis(1,2-benzenediolato(2-)-O,O')borate Li[B(C6O2)2] (LBBB) and combinations thereof.
38. The electrolyte according to claim 28, wherein the electrolyte further comprises an electrolyte binder.
39. The electrolyte according to claim 38, wherein the electrolyte binder is a polyether-type polymer binder, a fluorinated polymer or a water-soluble binder.
40. The electrolyte according to claim 39, wherein the fluorinated polymer binder is polyvinylidene fluoride (PVDF).
41. The electrolyte according to claim 34, wherein n ranges from 5 to 300.
42. An electrochemical cell comprising a cathode, an electrolyte and an anode, wherein the cathode comprises the electrode material of any one of claims 16 to 26.
43. An electrochemical cell comprising a negative electrode, an electrolyte and the positive electrode of claim 27.
44. An electrochemical cell comprising a cathode, an anode and the electrolyte of any one of claims 28 to 41.
45. An electrochemical cell comprising a negative electrode, an electrolyte and a positive electrode, wherein the positive electrode is as defined in claim 27 and the electrolyte is as defined in any one of claims 28 to 41.
46. A lithium battery comprising the electrochemical cell of any one of claims 42 to 45.
Citation Information
Patent Citations
PASSI terpolymer and preparation method thereof
CN101704950A
Redox-Active Supramolecular Polymer Binders Derived from Perylene Bisimide Nanowires Enable High-Rate Lithium-Sulfur Batteries
US20170279122A1
Novel photoinitiators and applications therefor
WO1999054363A1